Dinamika fluks CO2 pada perkebunan kelapa sawit di lahan gambut - M. Joehari Jamili; Budi Nugroho; Basuki Sumawinata; Syaiful Anwar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
CO2 flux from peat soil planted with oil palm is temporally and spatially dynamic, which is related to various environmental factors. This flux can be partitioned into fluxes from oil palm root respiration, litter decomposition, and peat material decomposition. The aim of this study was to determine the temporal and spatial dynamics of CO2 fluxes, the contribution of oil palm roots respiration, the contribution of litter decomposition, and the relation between flux and environmental factors in oil palm plantations on peatland. Measurements of CO2 flux using an infrared gas analyzer (IRGA) were carried out in harvesting path and inter raw of oil palm plantation, and nearby bushland. Flux measurements were repeated every three to four days for almost five months. Results showed the dynamics of the CO2 fluxes temporally and spatially. Temporally, CO2 flux in oil palm plantation and bushland ranged from 2.9 – 11.1 and 0.5 – 6.4 g C-CO2 m2/day, respectively. Spatially, the flux in oil palm plantation and bushland ranged from 4.8 – 8.8 and 2.7 – 3.4 g C-CO2 m2/day, respectively. The contribution of oil palm roots respiration and litter decomposition were 48.4 and 5.8%, respectively. These results confirm that plant roots respiration plays an important role in the release of carbon from the soil surface.